2011
DOI: 10.1007/s11136-011-9906-7
|View full text |Cite|
|
Sign up to set email alerts
|

Reliability and validity of the Taiwan (Mandarin Chinese) version of the chronic respiratory questionnaire

Abstract: The Taiwan version of the CRQ shows good validity, internal consistency, and test-retest reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…It may also lack sensitivity in patients with minor symptoms 74. This widely used questionnaire is available in several languages 7578…”
Section: Pro Instruments For Key Copd Conceptsmentioning
confidence: 99%
“…It may also lack sensitivity in patients with minor symptoms 74. This widely used questionnaire is available in several languages 7578…”
Section: Pro Instruments For Key Copd Conceptsmentioning
confidence: 99%
“…Test-retest examines item stability using the same measures administered to participants at two different occasions within a chosen time period. The test-retest procedure has been applied to many culturally- and linguistically-translated instruments [ 45 - 47 ]. Allen and Yen [ 48 ] explained that using a very short time interval between tests could cause carryover effects due to memory, practice, or mood.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the relationship between exercise capacity and fatigue has been studied more extensively (n=15) compared with the association between peripheral muscle strength and fatigue (n=3) (online supplementary table 5 and figure 2). Of the 15 studies investigating the association of fatigue with exercise capacity, five did not find significant associations [14,37,43,56,57], four found significant but weak associations (r=−0.29 to r=−0.14) [16,41,54,59], three observed significant moderate associations (r=−0.35 to r=−0.30) [49,55,62], and three studies found significant strong relationships (r=−0.77 to r=−0.55) [13,15,25]. Exercise capacity was mostly studied with the 6-min walk test (6 MWT; n=12), followed by the symptom-limited cycle exercise test (n=2), and the incremental shuttle walk test (ISWT; n=1).…”
Section: Physical Factors Associated With Fatigue Exercise Capacity and Peripheral Muscle Strengthmentioning
confidence: 99%
“…Nine studies examined the association between fatigue and health-related quality of life (HRQoL) [16,27,49,54,56,62,[72][73][74] (online supplementary table 6 and figure 2). One out of nine studies reported a nonsignificant association (p>0.05) between fatigue and HRQoL [72].…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation